The corporate saving glut and the current account in Germany - Thorsten Klug; Eric Mayer; Tobias Schuler (European Central Bank (ECB), 2021)
We investigate, in the case of Germany, the positive correlation between the cyclical components of the corporate saving glut in the non-financial corporate sector and the current account surplus from a capital account perspective. Employing sign restrictions, our findings suggest that mostly labor supply, world demand and financial friction shocks account for the joint dynamics of excess corporate saving and the current account surplus. Household saving shocks, by contrast, cannot explain the correlation. We conclude that, explained through these factors, the corporate saving glut is an important driver of the cyclical component of the current account.
Keywords: E32; F32; F45; 330; Current account; corporate saving; macro shocks